A Living Cell Repository of the Cranio-/Orofacial Region to Advance Research and Promote Personalized Medicine - Parisi, Ludovica; Knapp, Patrick O.; Girousi, Eleftheria; Rihs, Silvia; La Scala, Giorgio C.; Schnyder, Isabelle; Stähli, Alexandra; Sculean, Anton; Bosshardt, Dieter D.; Katsaros, Christos; Degen, Martin (Frontiers in Cell and Developmental Biology, 2021)
The prevalence of congenital anomalies in newborns is estimated to be as high as 6%, many of which involving the cranio-/orofacial region. Such malformations, including several syndromes, are usually identified prenatally, at birth, or rarely later in life. The lack of clinically-relevant human cell models of these often very rare conditions, the societal pressure to avoid the use of animal models and the fact that the biological mechanisms between rodents and human are not necessarily identical, makes studying cranio-/orofacial anomalies challenging. To overcome these limitations, we are developing a living cell repository of healthy and diseased cells derived from the cranio-/orofacial region. Ultimately, we aim to make patient-derived cells, which retain the molecular and genetic characteristics of the original anomaly or disease in vitro, available for the scientific community. We report our efforts in establishing a human living cell bank derived from the cranio-/orofacial region of otherwise discarded tissue samples, detail our strategy, processes and quality checks. Such specific cell models have a great potential for discovery and translational research and might lead to a better understanding and management of craniofacial anomalies for the benefit of all affected individuals.